Pengaruh Pemanfaatan Fitur Virtual Try-On Berbasis Augmented Reality pada Aplikasi Tiktok dalam Pemilihan Produk Cushion Oleh Mahasiswa di Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang - Thalita Salsabilla Kasuma; Rahmi Oktarina (Institut Nalanda, 2024)
This research is motivated by problems. The digital era has had a significant impact on social, economic and cultural aspects, especially in the field of information technology. Information technology is an ever-growing field that enables the exchange and sharing of information. The application of digital marketing is currently increasingly being carried out considering that industrial competition, especially in the e-commerce sector, is getting tighter. As one of the largest e-commerce in Indonesia, Tiktok has adopted the use of augmented reality virtual try on technology as one form of its digital marketing efforts to create a more enjoyable user experience. This research was conducted with the aim of analyzing the effect of using the virtual try-on feature based on augmented reality on the Tiktok application by Generation Z. This research took a study of the virtual try-on feature found on Indonesian Tiktok e-commerce for beauty products. This research used a quantitative approach through causal associative techniques on 264 respondents who were interested in Cushion products. Data analysis in this research was obtained using PLS-SEM which showed the results that the dimensions of the augmented reality variables had a positive effect on product selection at Cusion.